PENGARUH MOTIVASI BELAJAR, SELF EFFICACY DAN PROKRASTINASI TERHADAP PERILAKU KECURANGAN AKADEMIK MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA DALAM MENYELESAIKAN TUGAS AKHIR - Putri Maulida, Nabila; Susanti, Santi; Fauzi, Achmad (Transpublika Publisher, 2023)
This study aims to determine whether there is an influence between learning motivation and procrastination on academic fraud behavior in students of the Faculty of Economics, Jakarta State University in completing their final assignment. The population in this study were students of the Faculty of Economics, Jakarta State University class of 2019 who were in the process of completing their final project, with an affordable population of 402 students. The sampling technique used proportional random sampling with a total sample of 201 respondents. The research method used is a quantitative method with a questionnaire or survey model. The research analysis method is a descriptive statistical test, validity test, reliability test, normality test, linearity test, multiple linear regression analysis, coefficient of determination (R2 Square), and hypothesis testing (T test and F test). The results of testing the data that has been done show that learning motivation has a negative and significant effect on academic fraud behavior, self-efficacy has a negative and significant effect on academic fraud behavior, procrastination has a positive and significant effect on academic fraud behavior and lastly learning motivation, self-efficacy and procrastination together - equally influential and significant to academic fraud behavior.